Respuesta :

Answer:

[tex]f^{-1}(x)=2(+/-)2\sqrt{(7+x)}[/tex]

Step-by-step explanation:

we have

[tex]2(x-2)^{2}=8(7+y)[/tex]

step 1

Exchange x for y and y for x

[tex]2(y-2)^{2}=8(7+x)[/tex]

step 2

isolate the variable y

[tex](y-2)^{2}=4(7+x)[/tex]

take the square root both sides

[tex]y-2=(+/-)\sqrt{4(7+x)}[/tex]

[tex]y=2(+/-)\sqrt{4(7+x)}[/tex]

step 3

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=2(+/-)\sqrt{4(7+x)}[/tex]

[tex]f^{-1}(x)=2(+/-)2\sqrt{(7+x)}[/tex]  ----> equation of the inverse

Answer:

y=2+√28+4x

Step-by-step explanation:

ACCESS MORE